Tracks Of Syekh Musthafa Husein's Theological Education - Hairullah, Hairullah; Katimin, Katimin; Daulay, Maraimbang; Adenan, Adenan; Salamuddin, Salamuddin (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to find out what the educational process of Sheikh Musthafa Husein was like during childhood and adulthood. Then this research also aims to find out the traces of the theological education of Sheikh Musthafa Husein at the Purba Baru Musthafawiyah Islamic Boarding School. The method used by researchers in this research is a qualitative research method with a character study type. In the results of this research, it was found that Sheik Musthafa Husein, whose childhood name was Muhammad Yatim, was born in 1886 AD/1303 H. in the village of Tano Bato. After the congregational morning prayer at the mosque, he remained in the mosque until the time for the dhuha circumcision prayer, then returned home to have breakfast with his family. After breakfast, go to Maktab/Madrasah until near noon time. After midday prayers in congregation at the mosque, he returned home to have lunch with his family, then went to the garden with his students until Asr time approached. After the Asr prayer in congregation at the mosque, we returned home to gather with our family while sitting around and playing with the children in the yard until just before Maghrib time. Just before Maghrib's time, he went to the mosque along with several of his students. Some of the students brought lamps, and some also brought books that would be studied after completing the Maghrib prayer. The students sat in a circle, and the teacher (Syekh Musthafa Husein) sat in the middle on a bench/chair. This recitation takes place only between Maghrib and Isha every day. After finishing the Isha prayer in the congregation, he returned home with his students. At night, he always read the Koran until late, and at midnight, he always prayed the Tahajjuj prayer. When this Islamic boarding school was founded by Sheikh Musthafa Husein, he determined the lessons and knowledge taught by himself. This established curriculum refers to his educational experience while studying in Mecca (1900-1912). He once said that at the Musthafawiyah Islamic Boarding School Student Conference in 1952 in Purbabaru, which was attended by thousands of his students and the surrounding community, he said: O my children, I need to convey on this occasion that the lessons and knowledge that I provide are the same. With what I learned while studying Islam in Mecca, for this reason I ask that the Islamic knowledge that I have given be passed on to all my children. The Islamic education system built by Sheikh Musthafa Husein since its founding is classical, namely with a tiered model, namely grades one to seven. This level of education is different from the current education system, which only lasts three years at the Tsanawiyah level and three years at the Aliyah level.